Kapitalisasi Tipis, Campuran Aset, Penghindaran Pajak - Aprilina, Vita (JRAK: Journal of Accounting Research and Computerized Accounting, 2021)
This study aims to examine the acceptance of asset mix, thin capitalization on tax avoidance. This study uses secondary data from financial report and annual report. The populatioan in this study were all pharmaceutical companies listed on the Indonesia Stock Exchange in 2015-2019 and the sample was taken using a purposive sampling technique with several criteria for sampling. Data analysis in this study used multiple linear regression. The results showed that tin capitalization had a positive effect on tax avoidance, while the asset mix proxied by inventory intensity had no effect on tax avoidance.